Minneapolis Madams: The Lost History of Prostitution on the Riverfront - Hinther, Rhonda L. (Labour / Le Travail, 2015)
The article reviews the book, "Minneapolis Madams: The Lost History of Prostitution on the Riverfront," by Penny A. Peterson.